A pre- burial adsorption model for the genesis of gold in the Witwatersrand - R. J. Davidson (The Southern African Institute of Mining and Metallurgy, 1990)
The chemistry related to the adsorption of gold, uranium, and transition-metal ions onto algal biomass (activated carbon) is related to the genesis of the Witwatersrand. Detrital gold being washed into the early basin, together with cyanide generated in the atmosphere, would have solubilized as the stable aurocyanide complex, the necessary oxygen being produced from the photosynthesis of carbon dioxide by primitive algae. Pebble-type conglomerates, while providing for the free movement of solutions containing the vital nutrients for prolific algal growth, would have screened of the sunlight, which would otherwise have degraded any free cyanide in solution. With the subsequent decomposition of the algal deposits, it is surmised that carbon-rich layers having adsorptive properties similar to those of activated carbon formed in the conglomerates. Under these conditions, gold (silver) in solution would have been adsorbed selectively as the cyanide complex, together with uranium as the carbonate complex. Any transition-metal ions present would also have been adsorbed onto such a substrate. The subsequent burial and compression of the gold-rich conglomerate with temperatures rising to about 400DC would then have reduced the adsorbed gold to the metal in a single segregated gold-silver metal phase (95 to 99 per cent of the contained gold), while leaving behind a sulphide phase rich in iron, base metals, and arsenic and containing some gold and silver. The recrystalization of this later phase may explain the presence of the rather consistent contents of secondary pyrite in the Witwatersrand conglomerates. Similarly, uranium minerals, some rich in titanium and carbon, may also have formed. An adsorption model would explain the very consistent trends in the gold-to-silver ratios of individual reefs in the Witwatersrand, which suggest an extensive hydrothermal system approaching isothermal equilibrium. Also, as gold grades increase, so silver grades generally decrease, indicating the sequential displacement of silver by gold as classically obtained with activated carbon.